“English literature in global contexts: Arabic, Indian and Chinese literary readings” - DeCoursey, Christina A; Ganpule, Shilpagauri; Harb, Graziella; Atallah, Denise; Zaatari, Mona; Bakri, Mariam (Advances in Social Sciences Research Journal, 2015)
English-language literature holds a privileged place in global education. It is a central component of preparing second-language students, who expect to participate in the global knowledge economy, and who currently experience a global identity. Reading English-language literature is now part of the global student experience. This study uses Hofstede’s Values Survey Module data, and Appraisal analysis, to explore the responses of Lebanese, Indian and Chinese second-language students to an English-language poem. Participants wrote a personal response to an English translation of Tao’s “Returning to Live in the Country”. Responses were aggregated into corpuses, for analysis, first comparing response rates to Hofstede’s cultural dimensions scores for the national profile, and second for their subjective emotions, judgments and appreciations. Results indicate that readers mainly use local cultural values in responding to English-language literature. Participant groups diverged from their national profile in evaluating city and country life. Lebanese participants were more patriotic than the national profile. Indian participants were more focused on philosophic rewards than the national profile. Hong Kong participants’ criticisms of the English translation of the Chinese poem selected suggest their collectivism, and the role of literature in helping second-language students place themselves into global contexts.